RETRACTED: PRODUKSI DAN KARAKTERISASI BIOCHAR AMPAS TEBU(Saccharum officinarum Linn) PRODUCTION AND CHARATERIZATION OF BAGASSE BIOCHAR (Saccharum officinarum Linn) - Suparnawati Suparnawati; Warsidah Warsidah; Harlia Harlia; Anthoni Batahan Aritonang (Tanjungpura University, 2021)
This article has been retracted: please see IJoPAC Policy on Article Retraction (https://jurnal.untan.ac.id/index.php/IJoPAC/pages/view/PUBLICATIONETHICS). This article has been retracted at the request of the Editor. One of the stages of submitting a paper by the author for publication is ensuring that the paper has never been published in another publication. The use of data from other articles without including the source of the citation is an abuse of the scientific publishing system. We apologize to our readers that this was not detected during the submission process.